Which role for nitric oxide in symbiotic N2-fixing nodules: toxic by-product or useful signaling/metabolic intermediate? - Boscari, Alexandre; Meilhoc, Eliane; Castella, Claude; Bruand, Claude; Puppo, Alain; Brouquisse, Renaud (Frontiers in Plant Science, 2013)
The interaction between legumes and rhizobia leads to the establishment of a symbiotic relationship characterized by the formation of new organs called nodules, in which bacteria have the ability to fix atmospheric nitrogen (N2) via the nitrogenase activity. Significant nitric oxide (NO) production was evidenced in the N2-fixing nodules suggesting that it may impact the symbiotic process. Indeed, NO was shown to be a potent inhibitor of nitrogenase activity and symbiotic N2 fixation. It has also been shown that NO production is increased in hypoxic nodules and this production was supposed to be linked –via a nitrate/NO respiration process- with improved capacity of the nodules to maintain their energy status under hypoxic conditions. Other data suggest that NO might be a developmental signal involved in the induction of nodule senescence. Hence, the questions were raised of the toxic effects versus signalling/metabolic functions of NO, and of the regulation of NO levels compatible with nitrogenase activity. The present review analyzes the different roles of NO in functioning nodules, and discusses the role of plant and bacterial (flavo)hemoglobins in the control of NO level in nodules.